Obtención de información gerencial con cubos OLAP mediante el desarrollo de aplicación web de gestión escolar del instituto ITSI de Chone - Cedeño Zambrano, Adriana Elizabeth (2016)
In order to implementing a cube OLAP information through the development of a website application for the school management at ITSI educational unit Chone Canton province of Manabi, all the requirements for the development according to the needs of the institution were analyzed and then they demonstrated the technical results and documentation using the Scrum methodology because it allowed to perform the process of make deliveries partially and selected schedule, allowed correct errors in each stage and emphasized the implementation of the project. The SIGE ITSI application was developed using the paradigm of object-oriented programming defined by classes and functions, it avoided the code redundancy and helped the application to be more agile reducing times process up to 59.32%, the implementation of the application generated a positive impact in the society because it increased the credibility and prestige of the institution to be in constant technological growth. With the implemented cube greatly improved the process of scores reports reducing time up to 34.62%, also contributed to optimize taking decision through the analyzes of dynamic reports which is generated by the OLAP cube and in the future can be modeled other data schemes established from the cube.